Collagen-Derived N-Acetylated Proline-Glycine-Proline in Intervertebral Discs Modulates CXCR1/2 Expression and Activation in Cartilage Endplate Stem Cells to Induce Migration and Differentiation Toward a Pro-Inflammatory Phenotype. (20th November 2015) - Feng, Chencheng; Zhang, Yang; Yang, Minghui; Huang, Bo; Zhou, Yue
Abstract : The factors that regulate the migration and differentiation of cartilage endplate stem cells (CESCs) remain unknown. N -Acetylated proline-glycine-proline ( N -Ac-PGP) is a chemokine that is involved in inflammatory diseases. The purpose of this study was to detect N -Ac-PGP in degenerative intervertebral discs (IVDs) and to determine its roles in the migration and differentiation of CESCs. Enzyme-linked immunosorbent assay (ELISA) and liquid chromatography-mass spectrometry results indicated that the levels of the proteases that generate N -Ac-PGP as well as N -Ac-PGP levels themselves increase with the progression of IVD degeneration. Immunohistochemistry and an N -Ac-PGP generation assay demonstrated that nucleus pulposus (NP) cells generate N -Ac-PGP from collagen. The effects of N -Ac-PGP on the migration and differentiation of CESCs were determined using migration assays, RT-PCR, immunoblot analysis, and ELISA. The results showed that the expression of N -Ac-PGP receptors (CXCR1 and CXCR2) in CESCs was upregulated by N -Ac-PGP. Additionally, N -Ac-PGP induced F-actin cytoskeletal rearrangement in CESCs and increased CESC chemotaxis. Furthermore, N -Ac-PGP recruited chondrocytes and spindle-shaped cells from the cartilage endplate (CEP) into the NP in vivo. These spindle-shaped cells expressed CD105 and Stro-1 (mesenchymal stem cell markers). N -Ac-PGP induced the differentiation of CESCs toward a pro-inflammatory phenotype with increased production of inflammatory cytokines rather than toward an NP-like phenotype. Our study indicated that, in the complex microenvironment of a degenerative disc, N -Ac-PGP is generated by NP cells and induces the migration of CESCs from the CEP into the NP. N -Ac-PGP induces a pro-inflammatory phenotype in CESCs, and these cells promote the inflammatory response in degenerative discs. Stem Cells 2015;33:3558–3568